PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL DALAM MEMPERKENALKAN BUDAYA LOKAL BUGIS PADA SISWA SD 6/75 CORAWALI KABUPATEN BONE - Fatimah Mardani; Ulfiyah Azizah; Hasni; Ahmad Syawaluddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of science and technology encourages the world of education to utilize digital media in the learning process. The use of digital media has become one of the main focuses in the world of education, especially at the elementary school level. This study aims to analyze the use of digital learning media in introducing local Bugis culture as an effort to improve understanding to students. The methodology used in this study is a qualitative approach with data collection techniques through interviews and observations. The results of the study indicate that the use of digital learning media has a significant positive impact on student understanding. Teachers utilize digital learning in social studies learning, such as the use of projectors, interactive videos, PowerPoint, and online quizzes. Digital learning media has proven effective in strengthening students' understanding of aspects of local Bugis culture such as traditional clothing, traditional houses, traditional dances, and the values ​​contained therein. In addition, this media also increases student motivation and engagement during the learning process. However, challenges such as limited technological infrastructure, the digital divide, and the lack of teacher competence in using technology remain major obstacles. Therefore, efforts are needed to improve teacher capabilities through training and the provision of adequate technological facilities. This study concludes that digital media has significant potential to improve the quality of social studies learning, particularly in helping students introduce local Bugis culture, if supported by adequate infrastructure and improved teacher competency.